Acute oral toxicity study of seed, peel and pulp extracts from Ha Chau Burmese-grape (Baccaurea ramiflora Lour.) fruit using mice - Nguyen Hong Xuan; Nguyen Trong Ngu; Nguyen Cong Ha (Agriculture and Natural Resources, 2026)
Importance of the work: The first evidence of safety for human consumption was provided for Ha Chau (Baccaurea ramiflora Lour.) fruit extracts, addressing a critical gap in toxicological data. Objectives: To determine the acute oral toxicity profile of Ha Chau fruit peel, pulp and seed extracts in mice. Materials and Methods: Swiss albino mice received oral doses of ethanolic peel extract, ethanolic seed extract or pulp juice (5–5,000 mg/kg) using a fixed-dose procedure. Clinical signs, biochemical and hematological indices, organ weights and histopathology were evaluated for 14 d following the respective treatments. Results: All the treated groups had 100% survival with a dose above 5,000 mg/kg required to kill one-half of the tested members. The tested biochemical and hematological parameters remained within normal ranges. Organ weights (liver, kidney, spleen), morphological characteristics and histological findings were comparable between the treatment and control groups, indicating the absence of extract-induced alterations. Main finding: The Ha Chau fruit peel, pulp and seed extracts exhibited no acute toxicity at high doses, providing novel toxicological evidence supporting their safe use in functional food and pharmaceutical applications.